Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Free-ranging domestic cats (Felis catus) on public lands: estimating density, activity, and diet in the Florida Keys - Michael V. Cove; Beth Gardner; Theodore R. Simons; Roland Kays; Allan F. O’Connell (Biological Invasions, 2018)

Ecological diversification of the Australian Coptotermes termites and the evolution of mound building - Timothy R. C. Lee; Theodore A. Evans; Stephen L. Cameron; Dieter F. Hochuli; Simon Y. W. Ho; Nathan Lo (Journal of Biogeography, 2017)
Aim The Australian Coptotermes (Family: Rhinotermitidae) are a small monophyletic group of termites, some of which build mounds. In this study, we construct predicted distributions based on environmental data (niche models) for all Australian species of Coptotermes to test whether specific environmental factors have contributed to the evolution of mound‐building behaviour and whether the degree of niche similarity and degree of phylogenetic similarity are correlated. Location The Australian mainland, including the known native ranges of all Australian species of Coptotermes . Methods We estimated the phylogenetic relationships between the species of Australian Coptotermes . We then generated and compared environmental niche models in a phylogenetic framework for all study species to test niche conservation. Our analyses were based on location data from our own sampling and from the Atlas of Living Australia, genetic data from a previous study of Australian Coptotermes , and environmental data from WorldClim and ASRIS . Results We found that no environmental variable differed consistently between mound‐building and non‐mound‐building taxa and that the differences in niches between pairs of Australian species of Coptotermes are uncorrelated with time since divergence. The environmental tolerances of the Australian Coptotermes termites are more restricted by rainfall than they are by soil or temperature. Main conclusions Our results show that mound‐building behaviour has not necessarily evolved in response to similar abiotic conditions. Our results are consistent with ecological speciation leading to niche divergence since Coptotermes first arrived in Australia ~12.5 million years ago.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Mercury bioaccumulation in Southern Appalachian birds, assessed through feather concentrations - Rebecca Hylton Keller; Lingtian Xie; David B. Buchwalter; Kathleen E. Franzreb; Theodore R. Simons (Ecotoxicology, 2014)

A spatial mark–resight model augmented with telemetry data - Rahel Sollmann; Beth Gardner; Arielle W. Parsons; Jessica J. Stocking; Brett T. McClintock; Theodore R. Simons; Kenneth H. Pollock; Allan F. O'Connell (Ecology, 2013)
Abundance and population density are fundamental pieces of information for population ecology and species conservation, but they are difficult to estimate for rare and elusive species. Mark–resight models are popular for estimating population abundance because they are less invasive and expensive than traditional mark–recapture. However, density estimation using mark–resight is difficult because the area sampled must be explicitly defined, historically using ad hoc approaches. We developed a spatial mark–resight model for estimating population density that combines spatial resighting data and telemetry data. Incorporating telemetry data allows us to inform model parameters related to movement and individual location. Our model also allows Procyon lotor ) on South Core Banks, a barrier island in Cape Lookout National Seashore, North Carolina, USA. We estimated a population of 186.71 ± 14.81 individuals, which translated to a density of 8.29 ± 0.66 individuals/km 2 (mean ± SD). The model presented here will have widespread utility in future applications, especially for species that are not naturally marked.

Unmodeled observation error induces bias when inferring patterns and dynamics of species occurrence via aural detections - Brett T. McClintock; Larissa L. Bailey; Kenneth H. Pollock; Theodore R. Simons (Ecology, 2010)
The recent surge in the development and application of species occurrence models has been associated with an acknowledgment among ecologists that species are detected imperfectly due to observation error. Standard models now allow unbiased estimation of occupancy probability when false negative detections occur, but this is conditional on no false positive detections and sufficient incorporation of explanatory variables for the false negative detection process. These assumptions are likely reasonable in many circumstances, but there is mounting evidence that false positive errors and detection probability heterogeneity may be much more prevalent in studies relying on auditory cues for species detection (e.g., songbird or calling amphibian surveys). We used field survey data from a simulated calling anuran system of known occupancy state to investigate the biases induced by these errors in dynamic models of species occurrence. Despite the participation of expert observers in simplified field conditions, both false positive errors and site detection probability heterogeneity were extensive for most species in the survey. We found that even low levels of false positive errors, constituting as little as 1% of all detections, can cause severe overestimation of site occupancy, colonization, and local extinction probabilities. Further, unmodeled detection probability heterogeneity induced substantial underestimation of occupancy and overestimation of colonization and local extinction probabilities. Completely spurious relationships between species occurrence and explanatory variables were also found. Such misleading inferences would likely have deleterious implications for conservation and management programs. We contend that all forms of observation error, including false positive errors and heterogeneous detection probabilities, must be incorporated into the estimation framework to facilitate reliable inferences about occupancy and its associated vital rate parameters.

Discrimination of Nuclear Explosions against Civilian Sources Based on Atmospheric Xenon Isotopic Activity Ratios - Martin B. Kalinowski; Anders Axelsson; Marc Bean; Xavier Blanchard; Theodore W. Bowyer; Guy Brachet; Simon Hebel; Justin I. McIntyre; Jana Peters; Christoph Pistner; Maria Raith; Anders Ringbom; et al. (Pure and Applied Geophysics, 2010)

Evaluating Great Smoky Mountains National Park as a Population Source for the Wood Thrush - Theodore R. Simons; George L. Farnsworth; Susan A. Shriner (Conservation Biology, 2000)
The prevailing fragmentation paradigm predicts that large, intact forests are acting as population sources for Neotropical migrant landbirds. We used the Wood Thrush ( Hylocichla mustelina ) as a model for evaluating the role Great Smoky Mountains National Park (the largest national park in the eastern United States) may play in maintaining regional songbird populations. We estimated the annual productivity of Wood Thrushes in the park by combining observations on the birds' distribution, abundance, and productivity with estimates of habitat availability. We estimated a breeding population of approximately 10,000 nesting pairs using habitat models developed from over 2500 point‐count censuses conducted across the park. Data from 426 nests monitored from 1992 to 1997 produced a daily nest survival rate of 0.96. We estimated an annual fecundity of 2.76 fledglings per breeding pair, based on a model that incorporated the re‐nesting behavior of Wood Thrushes. Results indicate that the park is producing approximately 3000 surplus female young each year. Daily nest survival rates were below those reported in other studies of Wood Thrushes in large forest tracts. The relatively high productivity of 3.31 nestlings per successful nest suggests that, in the absence of predation, the park provides high‐quality nesting habitat for Wood Thrushes, but that it may also support a more diverse and abundant predator community than more disturbed or less contiguous sites. The difficulties of estimating the size of continental breeding bird populations make assessing the significance of the park within a regional landscape context problematic, but our estimates suggest that, although the park is functioning as a substantial population source on a local scale, its potential to sustain regional or continental Wood Thrush populations is limited. Our findings suggest that species such as the Wood Thrush are capable of moderate levels of surplus productivity in high‐quality habitat, but that extensive areas of suitable habitat outside protected areas and other public lands will be required to sustain continental breeding populations.